RIVAROXABAN HAS DEMONSTRATED AN ADVANTAGE OVER ACETYLSALICYLIC ACID IN PREVENTING THE RECURRENCE OF VENOUS THROMBOEMBOLIC EVENTS IN THE EINSTEIN CHOICE STUDY - . Editorial (Столичная издательская компания, 2017)
Press Release of Bayer AG